Kernel number response to plant density in tropical, temperate, and tropical × temperate maize hybrids - Cerrudo, Diego (2020)
Kernel set response to plant density was examined in terms of physiological processes underlying kernel set in temperate (Te), tropical (Tr), and temperate × tropical (TeTr) maize (Zea mays L.) hybrids. Four field experiments were performed in a subtropical environment, and treatments combined two new and popular commercial hybrids of each group of germplasm background with five plant densities (2–30 plants m−2). Determinations included plant growth rate (PGRS) and topmost ear growth rate (EGRS) during the period bracketing silking, grain yield, and its components. In all hybrids, kernel number was the main grain yield component contributing to grain yield variations across densities. When grown in a high‐yielding subtropical environment, all hybrids exhibited increased kernel number per area with increasing plant density from 5 to 11 plants m−2. There was not a clear trend among groups of germplasm background in the number of kernel set at each plant density, but distinctive physiological processes underlying kernel number per plant (KNP) were evident between Te and Tr hybrids. Across plant densities, the KNP/PGRS ratio was larger and PGRS was lower in Te than in Tr hybrids. Larger KNP/PGRS in Te than in Tr hybrids were associated with greater prolificacy al low plant density and larger EGRS. In TeTr hybrids instead, there was not a common physiological process underlying kernel set, since genotypes representing this group shared traits similar to those of Te and Tr genotypes.